The early animal radiation: insights from interpreting the Cambrian problematic fossils - Cong, Peiyun (Frontiers in Earth Science, 2023)
The genic and genomic data have been reshaping our understanding of the earliest radiation event of metazoans, the well-known Cambrian Evolutionary Explosion, not only from the respects of reshuffling phylogenetic topologies of some animal phyla but by deciphering the deep homologies of many morphological features. These advances, together with the continuing discoveries of the Ediacaran-Cambrian fossils, are unveiling the cladogenetic process of the early metazoans and the patterns of morphologic evolution during this biological radiation event. In this review, I focus on a small but challenging field, the paleobiology of the problematic fossils from the early Cambrian fossil Lagerstätten, mainly on controversies concerning their interpretation and the consequent impacts on understanding the early evolution of animals. The bizarre body plans of the early Cambrian problematica fossils alone do not account for the difficulties in studying their biology and affinity. Instead, the combined action of the taphonomic artifacts and the uncertainty in homologizing the preserved characters impede generating plausible interpretations. Despite all these, a testable and repeatable method for interpreting fossils has emerged and become more feasible. The integration of an evolutionary-grade conceptual frame is beneficial to the interpretation of the Cambrian problematic fossils. Together with the focus on taphonomic alternation and homologic assessment, the Cambrian problematic fossils are becoming more informative nodes in the ‘parsing tree’ of early animal evolution.